O último homem (1826): distopismo e profecia feminina no romance de Mary Shelley - Soares, Janile Pequeno (2020)
This research aims to analyze The Last Man (1826), a novel by the English writer Mary Shelley (1797-1851), from the perspective of the dystopian studies combined with feminist criticism, highlighting the female protagonism represented both by prophetic figures and by the female characters throughout the novel. The main theoretical resources were the studies of Clayes (2017), Moylan (2016), Vieira (2010), Queiroz (2014), Seymour (2000), Schmidt (2006), Funck (1998), Lefanu (1989) and Gilbert and Gubar (1984), among others. Published in 1826 The Last Man remains relevant to bring about a discussion that addresses the social fears of an era that continue to be a reality even centuries after its writing and publishing. The scenario is a speculated London between the years 2093 and 2100 and tells the story of a man, the only one immune to a plague spread at a pandemic level that destroys humanity as it was known until then. However, the novel goes further and builds the narrative evidencing the flaws of the human being, always based on individualistic principles, putting life in community at risk, also alert about the evils of its time of production while dressing the hope of change through the journal left by this last survivor. Thus, our analysis is centered on the elements that converge to create the dystopian quality of the novel, especially through the analysis of the journal of the character Lionel Verney, the survivor, among other factors that permeate the dystopianism in Mary Shelley's novel. The methodology used was analytical; discussions on the theme were confronted with the theory that supported the research.